Estimativa populacional e uso do hábitat do boto-cinza (Sotalia guianensis) no litoral sul do Rio Grande do Norte - Paro, Alexandre Douglas (2010)
Four areas are known as of frequent usage by Guiana dolphins (Sotalia guianensis) in the south coast of Rio Grande do Norte state, northeast Brazil: Tabatinga, Pipa, Lagoa de Guaraíras and Baia Formosa. This extension of 40 km of shoreline is under increasing anthropogenic impacts due to continuous development of the coastal areas and vessel traffic. The objective of this study was to investigate aspects of population biology and habitat use of the population of Sotalia guianensis in the south coast of Rio Grande do Norte. It was applied the photo-identification technique and posterior methods of capture-recapture for population estimation (POPAN extension in MARK). The distribution, movement and site fidelity of the dolphins were analyzed trough the geographic information system (GIS) and group characteristics and behavior trough non-parametric statistics. Field work was conducted on board a 10m motor vessel from March 2008 to March 2009. Photo-identification effort was 329h with 113h of direct observation of the dolphins. The population estimatives for each area: Tabatinga: 75 (63-92); Pipa 105 (88-129); Lagoa de Guaraíras: 27 (18-54) e Baia Formosa: 112 (89-129) individuals. Total population estimative was: 223 (192 a 297). High site fidelity was detected for only part of the population (<15%) as low site fidelity and transients individuals were also detected (>20%). It was observed frequent movements between Tabatinga, Lagoa de Guaraíras and Pipa, but not Baía Formosa. This suggests a division in two communities along this shore extension: one in Pipa and other in Baía Formosa. Group size was small, most groups with up to 10 dolphins. The areas were use intensively, only in Lagoa de Guaraíras dolphins were not seen in all field trips. Lagoa de Guaraíras is an area used by small groups exclusively for foraging. In Tabatinga and Pipa dolphins concentrated close to the shore, in the inner sector of the area and the main activity is also foraging. Significant larger groups were seen in socializing behavior but there was no difference in group size between the inner and external sectors of the area. The presence of calves and juveniles were significant greater in the inner areas of Tabatinga and Pipa, confirming the hypothesis that these beaches are also used for parental care. In Baia Formosa dolphins concentrated in the outer sector and foraging was also predominant. Significant larger groups were seen in the outer sector, mainly engaged in mixed behaviors of travel/foraging, possibly in some kind of group foraging. Calves and juveniles were significant more present in the outer sector where group size was also larger. In general there was no difference in area usage and period of the day. Sotalia guianensis has characteristics that make the species vulnerable to human activities such as small population concentrated in patches of suitable habitats restrict to coastal areas. We hope that this study bring new information for the species and help for the adequate management of the area in order to assure the presence of the dolphins as well as its behavior pattern and gene flow betweencommunities.